2009
DOI: 10.1103/physrevlett.103.235001
|View full text |Cite
|
Sign up to set email alerts
|

Quasimonoenergetic Electron Beams with Relativistic Energies and Ultrashort Duration from Laser-Solid Interactions at 0.5 kHz

Abstract: We investigate the production of electron beams from the interaction of relativistically-intense laser pulses with a solid-density SiO(2) target in a regime where the laser pulse energy is approximately mJ and the repetition rate approximately kHz. The electron beam spatial distribution and spectrum were investigated as a function of the plasma scale length, which was varied by deliberately introducing a moderate-intensity prepulse. At the optimum scale length of lambda/2, the electrons are emitted in a collim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 23 publications
8
52
0
3
Order By: Relevance
“…1b). Although there have been some observations of electron ejection from solid surfaces [30][31][32][33], the experimental parameters did not permit to reach the VLA regime we have identified in this work, the intensity being too low (< 10 19 W/cm 2 ) or the gradient scale length too long.…”
Section: Plasma Mirrors As Electron Injectorsmentioning
confidence: 86%
“…1b). Although there have been some observations of electron ejection from solid surfaces [30][31][32][33], the experimental parameters did not permit to reach the VLA regime we have identified in this work, the intensity being too low (< 10 19 W/cm 2 ) or the gradient scale length too long.…”
Section: Plasma Mirrors As Electron Injectorsmentioning
confidence: 86%
“…20 The diversity in the results can be explained by the fact that these experiments used different gradient scale lengths and intensities. Experiments with a controlled gradient 18,21 as well as numerical simulations showed that the electron emission is more efficient when the gradient scale length is around L ' k 0 =10. Evidently, the gradient scale length is a crucial parameter as it determines the dominant laser absorption mechanism: J Â B heating 22 and vacuum heating [23][24][25] at short L, resonant absorption 26 at intermediate L, or parametric instabilities at longer L.…”
Section: Articles You May Be Interested Inmentioning
confidence: 99%
“…[13][14][15][16][17] to few MeV. 18 Some experiments reported on beams emitted in the specular direction, 18 while others reported on beams emitted along the surface 19 or in the normal direction. 20 The diversity in the results can be explained by the fact that these experiments used different gradient scale lengths and intensities.…”
Section: Articles You May Be Interested Inmentioning
confidence: 99%
“…In some experiments, the energy spectrum of the electrons emitted from the plasma at a large angle of incidence of the laser beam on the solid target surface contained quasi-monoenergetic bunches of accelerated electrons, Refs. [19,20]. It was shown that a critically important factor in this case is the existence of preplasma, which is induced by the relatively low contrast of the laser pulse.…”
Section: Introductionmentioning
confidence: 99%